The reality of educational supervision in Najran from the point view of secondary school teachers and principals and their attitudes towards it - Al-Aqail, Nasser Salem (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the reality of educational supervision in Najran city from of secondary school teachers and principals point of view, the descriptive survey approach was used, and questionnaire consisting of (3) main areas and (32) paragraphs, applied to a sample of (282) school principals and teachers, including (226) teachers and (56) school principals of both sexes who work in secondary school education, The results indicated that the sample estimates of the reality of supervision at the level of the whole tool; got an overall average (3.25 out of 5), meaning a (medium) practice score, and the level of the three areas, they were in order; The field of educational supervision goals with the highest average (3.33), then the field of supervision methods with an arithmetic average (3.31), finally the field of supervisors' roles with an average of (3.14), all of which were of a medium degree, and the results indicated that there were differences in the attitudes of secondary school teachers and managers towards supervision for a variable. The job is on the total degree only without the fields and was in favor of the school leaders, and the results showed that there were no differences in the reality of supervision between teachers and leaders of the secondary stage towards supervision according to the gender variable, while there were differences in the reality of supervision according to the experience variable on the total degree of performance As well as on the three areas of the tool in favor of those with less experience (10 years or less) The results also showed that there are differences in the reality of supervision depending on the educational qualification variable in the first and second fields and in favor of the bachelor, as for the total degree and the third field of the tool, it was not Significant differences appear statistically. Based on the results, the researcher presented a set of recommendations and proposals for developing educational supervision in the city of Najran and the whole of the Kingdom.
Keywords: Attitudes; Educational supervision; Secondary school teachers and principals; Najran city